Circuit Design and Fusion Signal Processing Based on Uncertain Algorithm for Intelligent Wheel Speed Sensor of Integrated-Electronic-Parking-Braking System - Zheng, Zhu; Xiangyu, Wang; Liang, Li; Zhaonan, Li (IEEE International Conference on Industrial Informatics (INDIN), 2024)
Integrated-Electronic-Parking-Braking (EPBI) system is an important component of vehicles. Intelligent wheel speed sensor is the essential basic sensor of intelligent vehicle. The stable wheel speed signal is the key factor to realize EPBI control. Based on uncertain algorithm, a new type of circuit and fusion signal processing (FSP) is proposed, which solves the effective signal screening and signal fluctuation problem in traditional process system of intelligent wheel speed sensor. The wheel speed processing circuit includes an adjustable voltage regulator supply module (RSM) and signal processing module (SPM). On the basis of the circuit, FSP is designed, which can reduce the sensitivity of wheel speed signal to environmental noise to get a stable signal. The results show that this method processes the intelligent wheel speed signal effectively, improves the stability of wheel speed signal and ensure the basic braking function of EPBI.